Visitor Perceptions and Development Strategies for the Kanaga Hill Natural Tourism Object, Mount Ciremai National Park - Hendrayana, Yayan; Purnama, Ridwan; Adhya, Ilham (International Journal Administration, Business & Organization, 2024)
The purpose of this study was to determine visitor perceptions and development strategies for the Kanaga Hill tourism object. The method used is purposive sampling while for data analysis using a Likert scale and SWOT analysis. The results of visitors' perceptions of the Kanaga Hill tourism object produce a good scale value while for the development strategy: Kanaga Hill tourism object provides opportunities for the community to grow a better economy. The use of Kanaga Hill tourist objects for educational and research facilities. Adequate accessibility for tourists who visit. Promotion that has been going well to attract tourists to visit. The perception of visitors to Kanaga Hill tourism object is good from three variables, while for the development strategy there are four alternatives SO strategies that can be used are Kanaga Hill tourism objects provide opportunities for the community to grow a better economy and the use of Kanaga Hill tourism objects for educational and research facilities. Accessibility is adequate for visiting touristsand Promotion that has gone well to attract tourists to visit.